South African township residents describe the liminal potentialities of tourism. Issue 2 (14th March 2020) - Muldoon, Meghan L.
Abstract: The townships of South Africa are peri-urban neighbourhoods defined by racial segregation, economic disparity, and geographic isolation. A product of the racist policies of apartheid, these spaces exist as exclusively black or 'coloured' neighbourhoods that present limited opportunities for mobility for residents. Since the end of apartheid, townships have increasingly come up under the tourists' gaze as sites/sights of resistance, difference, and, urban adventure. While much of tourism scholarship on liminality to date has focused on tourism landscapes creating liminal opportunities for tourists, this paper details how tourism encounters may also become liminal opportunities for tourism hosts under certain conditions. While the tourism encounters take place in the familiar landscape that is home, they become liminal occasions in which to come face-to-face with the previously inaccessible Other and transform one's relationship with them, with themselves, and with their home space. In conducting a critical discourse analysis with the texts of interviews with 16 township residents, a number of liminal moments were identified in participants' descriptions of tourism encounters. Themes identified in this research include: (1) Pertaining to a change in social standing, economic state, relationships to/with the other; (2) Desire for engagement, transformation through encounter; (3) Transformation of one's understanding of the physical landscape, and; (4) Transformation of one's understanding of self. These themes are elucidated through the use of creative analytic practice (CAP) and demonstrate that while tourism encounters in the spaces of home do not involve a physical relocation, they can have a transformative effect in people for whom such encounters with the Other were previously forbidden.